2020
DOI: 10.3390/nu12113238
|View full text |Cite
|
Sign up to set email alerts
|

Laminaria japonica Suppresses the Atopic Dermatitis-Like Responses in NC/Nga Mice and Inflamed HaCaT Keratinocytes via the Downregulation of STAT1

Abstract: Atopic dermatitis (AD) is a skin allergy accompanied by acute and chronic dermal inflammation. In traditional oriental medicine, Laminaria japonica has been used to treat various diseases, including inflammatory diseases. Therefore, to determine the therapeutic potential of L. japonica against AD, we investigated the inhibitory effects of L. japonica water extract (LJWE) on the inflammatory mediators and AD-like skin lesions. We determined the cell viability of LJWE-treated HaCaT cells using the cell counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This reduces nasal rubbing [ 15 ] or clinical signs of atopic dermatitis, as well as inflammatory cytokine levels and leukocyte skin infiltrates [ 16 ] in these allergy models. Similarly, application of extracts from Costaria costata [ 17 ] and Laminaria japonica [ 18 ] reduce severity of allergic dermatitis and stimulate healing, possibly by decreasing inflammatory pathways in keratinocytes.…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces nasal rubbing [ 15 ] or clinical signs of atopic dermatitis, as well as inflammatory cytokine levels and leukocyte skin infiltrates [ 16 ] in these allergy models. Similarly, application of extracts from Costaria costata [ 17 ] and Laminaria japonica [ 18 ] reduce severity of allergic dermatitis and stimulate healing, possibly by decreasing inflammatory pathways in keratinocytes.…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
“…+ DNP i.n. challenge allergy ↓ nasal rubbing ↓ mast cell degranulation Proposed mechanism: Chlorophyll-C2 →↓ PI-3K + ↓ Btk, ↓ Syk active upon FcεR trigger →↓ Ca-mobilization [ 15 ] EtOH extract 10, 50, 100 mg/kg, 1×/day, 3 weeks Sargassum horneri female NC/Nga mouse; house dust mite/dayNCB skin sensibilization DNCB skin challenge (2×/week) allergy ↓ atopic dermatitis symptoms ↓ epidermal hyperplasia, hyperkeratosis, skin dryness ↓ mast cell + eosinophil skin infiltrates ↓ IL-25, IL-33 → ↓ Rantes (CCL5), Eotaxin (CCL11), TARC (CCL17) in skin ↓ IL-4, -5, -13, ↓ IL-6, -10, IFN-γ in serum ↓ spleen size increase ↓ IgG1, IgG2a increase [ 16 ] EtOH extract 100–300 mg/kg/day in diet, 5 weeks Costaria costata male NC/Nga mouse; DNCB-induced atopic dermatitis skin allergy allergy ↓ inflammatory cell and mast cell infiltration, epidermal thickness, erythema, hemorrhage, dead skin cell layers, skin dehydration ↓ Eotaxin and TARC (CCL17)↓ serum IgE and histamine normalization of spleen lymphocyte proliferation and cytokine production [ 17 ] water extract 100–300 mg/kg/day, 4 weeks Laminaria japonica female NC/Nga mouse; DNCB-sensitized and challenged dorsal skin allergy ↓ dermatitis severity; ↓ inflammatory mediators ↑ skin moisture in vitro: ↓ p38 MAPK,↑ ERK, ↓ STAT1 in HaCaT human keratinocyte cell line [ 18 ] dried powder 1–5–10%, 6 weeks Eisenia (=Ecklonia) arborea ...…”
Section: Table A1mentioning
confidence: 99%
“…Laminaria japonica is rich in polysaccharides and polyphenols, which are the primary substances with antioxidant and anti-inflammatory effects [ 19 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that Laminaria japonica specifically inhibits the nuclear translocation of the STAT1 gene through the MAPK pathway, reduces skin inflammation and the expression level of cellular inflammatory chemokines, and inhibits the loss of skin moisture in mice caused by dinitrochlorobenzene (NC/Nga) sensitization [ 18 ]. Fucoidan extracted from Laminaria japonica has been confirmed to reduce the content of tumor necrosis factor α (TNF-α) in THP-1 cells caused by lipopolysaccharide (LPS), and it can be reduced by 50% at 50 μg/mL [ 19 ]. Research on the anti-inflammatory activity of Laminaria japonica is emerging, but it remains blank in terms of UVB radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Nc/Nga mice aged 7–8 weeks were maintained on a high‐fat diet exacerbates the development of AD‐like symptoms (Jena et al, 2019). However, they were too young to show severe AD symptoms, which were developed after DNCB treatment of the dorsal skin (Hwang et al, 2020; Jeong et al, 2020). Jena et al (2019) reported that long‐term intake of high‐fat diets, corresponding to Western‐style diets, results in dermatitis by activating Th2 and Th17 cells in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%